Subjective patient-reported versus objective adherence to subcutaneous interferon β-1a in multiple sclerosis using RebiSmart®: the CORE study - Zecca, Chiara; Disanto, Giulio; Mühl, Sarah; Gobbi, Claudio (BMC neurology, 2017)
Background Patient adherence to treatment is key to preventing the worsening of neurological disability in multiple sclerosis (MS). The RebiSmart® autoinjector facilitates self-administration of subcutaneous interferon β-1a (sc IFN β-1a) and records objective adherence data. The CORE study was undertaken to evaluate the relationship between subjectively reported and objective adherence of MS patients using RebiSmart® in Switzerland and explore variables associated with objective adherence. Methods Patients with relapsing-remitting MS who were treated with sc IFN β-1a 44 or 22 μg three times weekly using RebiSmart® for at least 9 months participated in this phase IV non-interventional study. Neurologist questionnaires were used at month 0 to collect patient demographics, medical history and estimates of patients’ adherence. Patient questionnaires were used to record subjective patient-reported adherence at month 0 and estimates of variables influencing adherence. Objective adherence data were obtained from the RebiSmart® log-files at months 0 and 6. Results Of 56 patients who completed the observation period, 53 had evaluable data. Objective adherence differed significantly between self-reported compliant ( n = 33) and non-compliant groups ( n = 20) ( p = 0.00001). Older age, greater disability, patient’s perception of the importance of ease of use and storage, being well informed about RebiSmart® features and neurologists’ estimations of adherence were all positively associated with treatment adherence. Conclusions We showed for the first time that subjective patient-reported adherence in MS was well in line with objective adherence, suggesting that the frequency of administration is reported accurately by patients to their neurologist. This observation may have implications for future treatment monitoring strategies and strategic medical decisions. Patients, particularly those who are younger and with lower levels of disability, may benefit from being better informed of the importance of being adherent to their treatments and receiving information about their medication and the device they are using.